IMPLEMENTATION OF CHARACTER-BUILDING EDUCATION IN INCLUSIVE SCHOOLS - Fitri Meliani; Sati (Jurnal Cakrawala Pendas, 2023)
This study looks at how character education is practiced in inclusive schools, so that regular students and children with special needs (ABK) can learn together and respect each other. Children with special needs differ from ordinary pupils in their learning styles and modalities. Schools and teachers need to implement an approach so that regular students can tolerate ABK and ABK students can learn calmly without being bullied by regular students. The purpose of Permendiknas No. 70 of 2009 concerning Inclusive Education is to provide the greatest opportunity for all students to obtain quality education in accordance with their needs and abilities, regardless of whether they have intellectual potential or physical, emotional, mental, or social disorders. Child-friendly learning, empathy, learner-centered learning, and learning that matches children's learning needs are all characteristics of implementing inclusive character education in normal schools. Research data were collected through observation, interviews, and documentation. Data analysis includes data reduction, data visualization, and conclusions. Using triangulation sources and triangulation procedures, the data are tested for validity. The findings show that teachers in the sixth grade of Sekolah Sibghah Akhlak Quran Bekasi teach character through learning, modeling, reinforcement, and habituation. The values of tolerance and compassion are prioritized by the teacher in the classroom. Teachers do so by explaining ideas, discussing moral dilemmas, telling a story, encouraging active learning, and using a collaborative approach. In addition, teachers encourage their students to interact with their peers who have special needs both inside and outside the classroom by providing role models, rewards, and special supervision. Penelitian ini melihat bagaimana pendidikan karakter yang dipraktikan di sekolah inklusi, agar siswa regular dan anak berkebutuhan khusus (ABK) dapat belajar bersama dan saling menghormati. Anak-anak dengan kebutuhan khusus berbeda dari murid biasa dalam gaya belajar dan modalitas mereka. Sekolah dan guru perlu menerapkan pendekatan agar siswa regular bisa bertoleransi terhadap ABK dan siswa ABK dapat belajar dengan tenang tanpa mendapat perlakuan bullying dari siswa regular. Tujuan Permendiknas No. 70 Tahun 2009 tentang Pendidikan Inklusif adalah memberikan kesempatan sebesar-besarnya kepada seluruh peserta didik untuk memperoleh pendidikan berkualitas yang sesuai dengan kebutuhan dan kemampuannya, terlepas dari apakah mereka memiliki potensi intelektual atau gangguan fisik, emosional, mental, atau sosial. Pembelajaran ramah anak, empati, pembelajaran yang berpusat pada peserta didik, dan pembelajaran yang sesuai dengan kebutuhan belajar anak adalah semua karakteristik dari penerapan pendidikan karakter inklusif di sekolah normal. Data penelitian dikumpulkan melalui observasi, wawancara, dan dokumentasi. Analisis data meliputi reduksi data, visualisasi data, dan penarikan kesimpulan. Menggunakan sumber triangulasi dan prosedur triangulasi, data diuji validitasnya. Temuan menunjukkan bahwa guru-guru di kelas enam Sekolah Sibghah Akhlak Quran Bekasi mengajarkan karakter melalui pembelajaran, pemodelan, penguatan, dan pembiasaan. Nilai-nilai toleransi dan kasih sayang diprioritaskan oleh guru di kelas. Guru melakukannya dengan menjelaskan ide, mendiskusikan dilema moral, menceritakan sebuah kisah, mendorong pembelajaran aktif, dan menggunakan pendekatan kolaboratif. Selain itu, guru mendorong murid-muridnya untuk berinteraksi dengan rekan-rekan mereka yang memiliki kebutuhan khusus baik di dalam maupun di luar kelas dengan memberikan panutan, penghargaan, dan pengawasan khusus.